Primary Prevention of Ischemic Stroke - Sabayan, Behnam (Seminars in Neurology, 2022)
Ischemic stroke is by far the most common type of cerebrovascular event and remains a major cause of death and disability globally. Despite advancements in acute stroke care, primary prevention is still the most cost-effective approach in reducing the burden of ischemic stroke. The two main strategies for primary stroke prevention include population-wide versus high-risk group interventions. Interventions such as increasing access to primary care, regulation of salt and sugar contents in processed foods, public education, and campaigns to control cerebrovascular risk factors are examples of population-wide interventions. High-risk group interventions, on the other hand, focus on recognition of individuals at risk and aim to modify risk factors in a timely and multifaceted manner. This article provides an overview on conventional modifiable risk factors for ischemic stroke and highlights the emerging risk factors and approaches for high-risk group identification and treatment.
Keywords: prevention; ischemic stroke; population; high-risk